1998
DOI: 10.1126/science.279.5358.1913
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Surface Alloy Catalyst for Steam Reforming

Abstract: Detailed studies of elementary chemical processes on well-characterized single crystal surfaces have contributed substantially to the understanding of heterogeneous catalysis. Insight into the structure of surface alloys combined with an understanding of the relation between the surface composition and reactivity is shown to lead directly to new ideas for catalyst design. The feasibility of such an approach is illustrated by the synthesis, characterization, and tests of a high-surface area gold-nickel catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
673
0
13

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 978 publications
(693 citation statements)
references
References 15 publications
7
673
0
13
Order By: Relevance
“…However, the proposed alloy catalysts are not necessarily stable under harsh reaction conditions, especially, when these catalysts are in the form of nanoparticles. On the one hand, in order to optimize the reactivity and selectivity of alloy nanoparticle, certain surface composition is usually required [22,27,75]. On the other hand, the surface composition of alloy nanoparticles may change dramatically with the reaction conditions as shown by an ambient pressure XPS study on bimetallic nanoparticles carried out recently at Berkeley [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proposed alloy catalysts are not necessarily stable under harsh reaction conditions, especially, when these catalysts are in the form of nanoparticles. On the one hand, in order to optimize the reactivity and selectivity of alloy nanoparticle, certain surface composition is usually required [22,27,75]. On the other hand, the surface composition of alloy nanoparticles may change dramatically with the reaction conditions as shown by an ambient pressure XPS study on bimetallic nanoparticles carried out recently at Berkeley [84].…”
Section: Discussionmentioning
confidence: 99%
“…His contributions to the theories of surface chemical bonding and catalytic reaction over the past 30 years lead to a giant leap forward in our molecular level understanding of surface chemistry and heterogeneous catalysis [12][13][14][15][16][17][18][19][20][21]. Of course, his achievement is a result of his exceptional expertise in theoretical chemistry, but, from the point of view of an experimentalist, the more important factors perhaps are his willingness to work closely with experimentalists and his ability to grasp the essence of experimental development [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the kinetics of graphene nucleation may be decreased by increasing the epitaxial mismatch between the metal and graphene basal plane [11]. This can be done by the addition of alloying elements as for instance Cu [4,12,13], Sn [14,15,16] or Au [17,18]. These are alloying elements well-known to inhibit metal dusting.…”
Section: Introductionmentioning
confidence: 99%
“…As quoted in C & En News [9] "In decades past, basing a catalysis research program entirely on computation was unimaginable, nowadays excluding theory entirely is equally unimaginable". In fact, successful stories of new catalysts assisted by computational design have been reported [10,11].…”
mentioning
confidence: 99%